Enhancing spreadability of hydrogenation-dehydrogenation titanium powder and novel method to characterize powder spreadability for powder bed fusion additive manufacturing. (November 2022) - Il Kim, Young; Kim, Dae-Kyeom; Kim, InYeong; Cheol Park, Sang; Lee, Dongju; Lee, Bin
Graphical abstract: Highlights: Using hydrogenation-dehydrogenation(HDH) titanium(Ti) powder for powder bed fusion(PBF) with practical operation condition(recoating speed). Hydrophobic surface treatment of HDH Ti powder for improved flowability and mixing with spherical Ti powde. Recoating tester system was devised for mixed Ti powder using the same methodology as the actual PBF process in order to assess the spreadability of Ti powder. Optimizing PBF additive manufacturing conditions and heat treatment condition with PBF additive manufactured mixed Ti powder. Analysing of the mechanical properties and microstructure of additive manufactured specimens. Abstract: A low-cost hydrogenation–dehydrogenation (HDH) Ti powder was employed to reduce the cost of the material used in powder bed fusion (PBF) additive manufacturing. HDH Ti powder was hydrophobic surface-treated with methyltrichlorosilane and mixed with spherical powder at a 1:1 ratio to ensure flowability for PBF process. Subsequently, PBF process with practical recoating speed (50 mm/s) and heat treatment process were optimized. It was confirmed that a high specific strength structural material with interesting mechanical properties at a low cost was formed, with a tensile strength of 924 MPa and an elongation of 9.5 %. This paper also discusses an intuitive and accurate apparatus for measuring the spreadability of metal powders for PBF applications. A recoating tester was developed for direct quantification of the spreadability in PBF, and this confirmed the possibility of using the mixed Ti powder containing low price HDH Ti in PBF with practical recoating speed.